Gross architecture of ovarian specimens from a southwest Nigerian tertiary healthcare facility - Olaofe, Olaejirinde O.; Okongwu, Chigozie C.; Ewoye, Ese E.; Oladele, James O.; Soremekun, Ademola I.; Omoyiola, Oluwatosin Z. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The aim of our study is to describe the gross morphology of ovarian specimens and to see if some entities can be distinguished based on their gross morphology. Methods: We did a cross-sectional study of all ovarian specimen received by the department of morbid anatomy and forensic medicine of Obafemi Awolowo university teaching hospitals complex (OAUTHC), Ile-Ife, Nigeria from January 1, 2018, to December 31, 2022 (Five-year period). OAUTHC is situated in the southwestern part of Nigeria. Results: We examined 225 right ovarian specimens. Non- neoplastic lesions were the most common lesions of the right ovary accounting for 52 cases followed by malignant tumour accounting for 25 cases. We examined 233 specimens of the left ovary of which 133 were normal. Eighteen (72%) of malignant tumors of the left ovary had cystic cut surfaces. The spectrum of lesions of both ovaries has different average widest diameters with significant overlap in their distribution. Metastatic carcinoma is seen to involve both ovaries and found to mainly have a solid cut surface. We found that the average widest diameter of a normal left ovary is 3.6 cm while that of a normal right ovary is 4.9 cm. Conclusions: The ovarian lesions have different widest diameters and are usually larger than that of a normal ovary. Benign ovarian tumours are generally larger than their malignant counterparts but cannot be distinguished based on size alone. Metastatic carcinoma involved both ovaries and had a predominantly solid-cut surface. The normal left ovaries were smaller than the normal right ovaries.